PENGARUH INVESTASI ASING (PMA) DAN JUMLAH PENDUDUK TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN/KOTA DI PROVINSI KALIMANTAN BARAT TAHUN 2010-2014 - B01112074, Theresia Riska Pratiwi (Jurnal Pembangunan dan Pemerataan, 2017)
ABSTRACT Local revenue is part of the regional income sourced from the potential of the region itself levied by the local regulations in accordance with the legislation in force. The regional authority in conducting polling PAD intended that the area can fund the implementation of regional autonomy that is sourced from its own country. Local revenues derived from local taxes, regional retribution, the results of which are separated regional wealth management, and other legitimate PAD. This study aims to identify and analyze the Effect of Foreign Direct Investment (FDI) and the Population against revenue (PAD) in West Kalimantan Province. 2010-2014. Data analysis technique used is multiple regressionswith fixed effect model. Sources of data obtained from the Central Bureau of Statistics. Partially, the level of foreign investment and a significant positive effect on revenue with a significance level of 0.0188 <0.05. The population of positive and significant impact on revenue with a significance level of 0.0013 <0.05. Simultaneously, foreign direct investment (FDI) and the population significant effect on revenue significance of 0.0000 <0.05. Keywords: Foreign investment, Population, and source revenue